1998
DOI: 10.1159/000017903
|View full text |Cite
|
Sign up to set email alerts
|

Fumaric Acid Esters Suppress Peripheral CD4- and CD8-Positive Lymphocytes in Psoriasis

Abstract: Background: For severe forms of psoriasis vulgaris, the antipsoriatic fumaric acid esters (FAE) therapy has recently gained increasing acceptance and importance. Until today, there is little knowledge about the mode of action of FAE. However, some evidence exists indicating immunosuppressive effects. Objective: The aim of this study was to examine the systemic, particularly the immunological changes in patients suffering from psoriasis treated with FAE over a long period of time, since we expect to see pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
72
2
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 10 publications
15
72
2
4
Order By: Relevance
“…With a rate of 3.8%, our results regarding the occurrence of leukopenia are not as pronounced as the data published in the literature [6,[11][12][13] .…”
Section: Discussioncontrasting
confidence: 74%
“…With a rate of 3.8%, our results regarding the occurrence of leukopenia are not as pronounced as the data published in the literature [6,[11][12][13] .…”
Section: Discussioncontrasting
confidence: 74%
“…We now demonstrated that dimethylfumarate at a rather low concentration of 3 ÌM, which did not exhibit special antiproliferative activity, inhibited the IFN-Á-induced K17 overexpression. This finding adds another facet to the understanding of the obviously multimodal, partly anti-inflammatory and immunomodulating [36][37][38][39], and partly antiproliferative mechanism of the drug's action [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Flow-cytometric examinations of peripheral blood cells of psoriasis patients showedin parallel to the clinical effect of FAE treatment -decreased numbers of T and B lymphocytes but not of natural killer cells [24].…”
Section: Patient 2 Historymentioning
confidence: 91%